Biologics in atopic dermatitis. Issue 3 (June 2021) - Chan, Susan
Abstract : Purpose of review: Until recently there have been limited options for systemic therapy in atopic dermatitis, which is unresponsive to topical treatments. However, the last few years have seen a rapid progression in this field. The purpose of this review is to summarise some of the recent literature and ongoing studies in the field of biologicals in atopic dermatitis. Recent findings: Dupilumab has been shown to be effective in moderate to severe atopic dermatitis and is now licensed in the USA and Europe. Tralokinumab is currently under review by the Food and Drug Administration and the European Medicines agency. Phase 2 and 3 studies are taking place with other biological therapies. There is increasing evidence for the use of biologicals in children and for their role in multisystem disease. Summary: The recent breakthroughs in treatment represent an opportunity to resolve an unmet need; the management of atopic dermatitis which is unresponsive to topical therapy.